Impact of Impulse Control Disorders on Sleep-Wake Regulation in Parkinson’s Disease - Atbin Djamshidian; Werner Poewe; Birgit Högl (Parkinson's Disease)
Sleep disturbances are common in patients with Parkinson’s disease (PD) and are even more prevalent in patients with behavioural addictions, such as pathological gambling, compulsive sexual behaviour, compulsive buying, binge eating, punding, and the compulsive use of dopamine replacement therapy. An overview of the relationship between these impulse control disorders and sleep disturbances is given and potential underlying mechanisms and treatment strategies are covered.